367 Evaluation of the impact of legislative reform on worker fatalities, New Zealand. (20th November 2022) - Lilley, Rebbecca; Davie, Gabrielle; McNoe, Bronwen; Horsburgh, Simon; Driscoll, Tim; Cryer, Colin
Abstract : Amongst industrialised Commonwealth nations Occupational Health and Safety (OHS) legislation based on the Robens model of self-management of occupational risks is used for OHS improvements in the workplace. This study estimates the impact of the adoption of the Robens model to control the risk of work-related fatal injury (WRFI) in New Zealand. Methods: Population-based comparison of WRFI in workers aged 15–84 years occurring during three periods: before legislative reform (pre:1985–1992), after (post-1:1993–2002) and following a subsequent amendment (post-2:2003–2014). Annual age-industry standardised rates were calculated with 95% confidence intervals (CI). Age-adjusted annual percentage changes (APC) for each period, overall and stratified by high-risk industry and occupation groups were estimated using multivariable Poisson regression. Results: Over the 30-year period, 2, 053 worker deaths met the eligibility criteria. APC in age-adjusted WRFI rates changed little between periods: pre (-2.8%, 95% CI -5.5%, 0.0%); post-1 (-2.9%, 95% CI -4.5%, -1.3%) and post-2 (-2.9%, 95% CI -4.4%%, -1.3%). There was no evidence of differences in slope between periods. Variable trends in WRFI were observed for historically high-risk industry and occupational groups. Conclusions: Overall, the rate of worker WRFI decreased steadily over the 30 year period and there was no evidence of interruption in rates of decline greater than the previous prescriptive legislation. Beyond headline figures, historically high-risk groups had highly variable progress in reducing worker WRFI following legislative reform. Learning Outcomes: This study demonstrates the value of including pre-reform data and high-risk sub-group analysis when assessing the performance of OHS legislative reforms to control occupational risks.